ANALYSIS OF THE IMPLEMENTATION OF THE RAW MATERIAL INVENTORY INFORMATION SYSTEM AT MSMES MAWAR BAKERY & CAKE SHOP - Desi Mutiara Dini Rumapea; Winda Krisdianti Zendrato; Ryndian Gusty; Nursiah Nursiah; Jenni Sari Tarigan (INTEGRATIVE : Journal of Economics, Management, Business and Accounting, 2026)
This research aims to analyze the implementation of a Raw Material Inventory Information System at Mawar Bakery & Cake Shop, specifically at the Setia Budi branch in Medan. Although Mawar Bakery has implemented digitalization in sales through the use of Point of Sale (POS) systems, the management of raw material inventory is still carried out manually using bookkeeping and daily reports. This condition causes several problems, including inaccurate stock data, delayed reporting, the risk of human error, a lack of information synchronization between divisions, and low digital literacy among employees. The research approach used a descriptive qualitative method with data collection techniques through direct interviews with SPG staff and observation of daily operations. Analysis was conducted using Miles & Huberman’s theory and the Technology Acceptance Model (TAM), which assesses two key factors of technology acceptance: perceived usefulness and perceived ease of use. The study’s results indicate that the staff recognize the benefits of the digital system but still face obstacles in ease of use due to a lack of training and the absence of a digital-based SOP. This research finds that inventory digitization is essential to improve stock accuracy, production process efficiency, reporting speed, and the accuracy of managerial decision- making. Key recommendations include implementing a cloud-based inventory system, integrating POS with the inventory system, providing digital literacy training for all employees, upgrading technology infrastructure, and conducting regular system evaluations. By implementing these strategies, Mawar Bakery has the potential to improve operational efficiency, reduce manual errors, and strengthen its competitiveness as a modern bakery SME.